Performance of lightweight foamed concrete using palm oil clinker crushed (POCC) as sand replacement - Muhammad Jahiduddin, Abu Jamal (2011)
Palm oil industry is one of the most important Argo industries in Malaysia. Annually, large amounts of solid waste of palm oil residue are not utilized as a functional wastage and affect the environmental problems. Through public concerns and research effort, the agro waste by-product materials have potential to be utilized as construction material to replace conventional sand. In this study, the effectiveness of agro waste clinker by-product namely palm oil clinker crushed (POCC) was developed as an alternative material to replace the sand. In this present study, the effect of using different percentage of POCC to lightweight foamed concrete (L WC) due to compressive strength and elastic modulus were investigate. Four series of mix formulation L WC were prepared comprise of 0%, 5%, 10% and 15% as sand replacement from the total weight of sand. All the L WC specimens were cured in air curing for different curing ages namely 7, 28 and 60 days. The result revealed that by replacing the sand with POCC to L WC were significantly affect the compressive strength. The compressive strength also improved due to increasing the curing days. On the other hand, the modulus of elastic was improved significantly by increasing the percentage of POCC due to different curing days. It is noted that the optimum mix design to produce LWC-POCC was obtained by using 10% of POCC as sand replacement.